Determining Equivalence of Expressions: An Automated Evaluator's Perspective - Sharma, K. K.; Banerjee, Kunal; Mandal, Chittaranjan (2015 IEEE Seventh International Conference on Technology for Education (T4E), 2015)
As the intake of students is increasing in the institutions, fast and consistent evaluation of students' performance is becoming difficult without automated means of assessment. Programming assignments submitted by the students can be automatically assessed using an automated evaluator, which compares a program written by a student with a model program supplied by the instructor in order to evaluate the student's performance. In course of checking equivalence between the two programs, the evaluator sometimes has to determine whether some expression used in the student program assumes the same value as that of the model program or not. Thus, determining equivalence between pairs of expressions is at the core of designing automated evaluators. This paper proposes a novel technique to determine equivalence between expressions involving floating point and transcendental numbers, which have not been addressed in earlier literature to the best of the authors' knowledge.